The Forsyte Saga - Complete - Galsworthy, John, 1867-1933 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Forsyte Saga - Complete" by John Galsworthy is a series of three novels and two interludes published between 1906 and 1921. It chronicles the lives of an upper-middle-class English family acutely conscious of their "new money" status. At its center is Soames Forsyte, a solicitor who views himself as a "man of property" through his material possessions, yet finds no happiness. The saga explores marital discord, forbidden love, and family secrets that span generations, as the Forsytes navigate desire, betrayal, and the consequences of past actions. (This is an automatically generated summary.)
The Man of Property -- Indian Summer of a Forsyte -- In Chancery -- Awakening -- To Let.
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Forsyte_Saga
Release date is 2006-06-14
Produced by David Widger
Keywords: England -- Social life and customs -- 19th century -- Fiction; Domestic fiction; Women -- England -- Fiction; Middle class -- England -- Fiction; England -- Social life and customs -- 20th century -- Fiction; Forsyte family (Fictitious characters) -- Fiction; Families -- England -- Fiction